The Influence of The Social Environment and Modern Culture on The Financial Expenditure Pattern of Students of The Loli Student Association Throughout Malang Region - Daniel Wona Baga; Gunawan, Cakti Indra; Moch Nurhidayat (International Journal of Management and Business, 2025)
The social environment and contemporary culture play a crucial role in addressing student financial issues. This study aims to find out and analyze the influence of the social environment and modern culture on the financial expenditure pattern of students of the Loli Student Association Throughout Malang Region partially and simultaneously. The study employs quantitative methods, with data gathered via a questionnaire. For data analysis, the researcher utilizes multiple linear regression in the SPSS software. The results of the study prove that the social environment partially affects the pattern of student financial expenditure with a t-value of 3.555 and a t-table of 1.660 and modern culture affects the pattern of student financial expenditure with a t-value of 7.843 and a t-table of 1.660. Then simultaneously the social environment and modern culture affect the pattern of student financial expenditure with an F value of 116.665 and an F table of 2.21. The conclusion of this research is the Social environment has a significant effect on financial expenditure patterns of Students of The Loli Student Association Throughout Malang Region. Then, the modern culture variable has a significant effect on the financial expenditure patterns of Students of The Loli Student Association Throughout Malang Region. Last, the social environment and modern culture together or simultaneously, have a positive and significant effect on the financial expenditure patterns of Students of The Loli Student Association Throughout the Malang Region. The development of the next research can be examined by using other variables and other variable indicators that are more relevant in measuring the variables used, so that different and more accurate results can be obtained.